Supervisi Klinis Kepala Sekolah dalam Meningkatkan Kualitas Pembelajaran SMAN Musi Rawas - Lilis Merlita; Angga Pratama; Rahmuje Emawanalu; Desi Eka Citra Dewi (Al-Khair Journal: Management Education, 2024)
Abstract: School principals still have difficulty improving the quality of learning, marked by difficulties in conducting clinical supervision such as leading teachers to improve programs and process implementation as well as evaluating learning outcomes. The purpose of the study was to describe the clinical supervision of school principals in an effort to improve the quality of learning. Using descriptive qualitative methods, data collection through observation, interviews, documentation. The results of the study can be concluded that teachers have been accustomed to issuing complaints in learning with peers and leaders and hope to get solutions through clinical supervision, Efforts to improve the quality of teacher learning have been carried out by the principal through clinical supervision through three stages, namely the initial stage, the observation stage and the follow-up stage including planning, implementing, and evaluating learning programs. Obstacles encountered in clinical supervision are changes in curriculum and lack of activity of principals, supervisors and the Office of Education in improving clinical supervision capabilities. The solution carried out by the principal is to form a Supervision Team consisting of senior civil servant teachers and build intensive and effective communication regarding the importance of clinical supervision. So that it can be suggested to improve the quality of learning, then increase the clinical supervision of the principal of the principal. Keywords: Clinical supervision, principal, quality of learning, Musi Rawas State High School Abstrak: Kepala sekolah masih kesulitan meningkatkan kualitas pembelajaran ditandai dengan masih kesulitan melakukan supervisi klinis seperti memimpin guru memperbaiki program dan pelaksanaan proses serta evaluasi hasil pembelajaran. Tujuan penelitian untuk mendeskripsikan supervisi klinis kepala sekolah dalam upaya peningkatan kualitas pembelajaran. Menggunakan metode kualitatif deskriptif, pengumpulan data melalui observasi, wawancara, dokumentasi. Hasil penelitian dapat disimpulkan bahwa guru telah terbiasa mengeluarkan keluh kesahnya dalam pembelajaran dengan teman sejawat maupun pimpinan serta berharap mendapat solusi melalui supervisi klinis, Upaya peningkatan kualitas pembelajaran guru telah dilakukan oleh kepala sekolah melalui supervisi klinis melalui tiga tahapan yaitu tahap awal, tahap observasi dan tahap tindaklanjut meliputi perencanaan, pelaksanaan, dan evaluasi program pembelajaran. Kendala yang ditemui pada supervisi klinis yaitu adanya perubahan kurikulum dan kurang aktifnya kepala sekolah, pengawas dan Kantor Dinas pendidikan dalam meningkatkan kemampuan supervisi klinik. Adapun solusi yang dilakukan kepala sekolah yaitu membentuk Tim Supervisi yang anggotanya terdiri dari guru PNS senior dan membangun komunikasi yang intensif dan efektif terkait pentingnya supervisi klinis. Sehingga dapat disarankan untuk meningkatkan kualitas pembelajaran, maka tingkatkanlah supervisi klinik kepala sekolah kepala sekolah.Kata Kunci: Supervisi klinis, Kepala sekolah, kualitas pembelajaran, Sekolah Menengah Atas Negeri Musi Rawas